2011
DOI: 10.1103/physrevd.83.023516
|View full text |Cite
|
Sign up to set email alerts
|

Density perturbations in braneworld cosmology and primordial black holes

Abstract: We study, by numerical methods, the time evolution of scalar perturbations in radiation era of Randall-Sundrum braneworld cosmology. Our results confirm an existence of the enhancement of perturbation amplitudes (near horizon crossing), discovered recently. We suggest the approximate solution of equations of the perturbation theory in the high energy regime, which predicts that the enhancement factor is asymptotically constant, as a function of scale. We discuss the application of this result for the problem o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 55 publications
(90 reference statements)
0
27
0
Order By: Relevance
“…In this case, the power spectrum can be in agreement with the CMB data [12,16]. The fast waterfall phase itself has been the object of recent attention, especially to determine the contribution of iso-curvature perturbations [17][18][19][20][21][22] as well as the level of non-Gaussianities [23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 66%
“…In this case, the power spectrum can be in agreement with the CMB data [12,16]. The fast waterfall phase itself has been the object of recent attention, especially to determine the contribution of iso-curvature perturbations [17][18][19][20][21][22] as well as the level of non-Gaussianities [23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 66%
“…We have verified that the ellipticities become unobservably small by the time the inspiral enters the LIGO band, but they may be detectable in future experiments [42]. Mutiply-lensed quasars [43,44], pulsar timing arrays [45], and FRB lensing searches [46] may also allow probes of the ∼ 30 M PBH mass range.…”
Section: Gpcmentioning
confidence: 99%
“…[3], we suggested that if ∼ 30 M primordial black holes (PBH) make up the dark matter [17][18][19], then the rate for the merger of such events is consistent with the range inferred from the first LIGO events. PBHs in the mass range 20−100 M remain viable DM candidates [20,21]-lower masses are ruled out by null microlensing searches [22][23][24][25][26] and pulsar-timing-array searches [27], and higher masses by the dynamics of wide stellar binaries [21,28,29]. Ref.…”
Section: Introductionmentioning
confidence: 99%